Impact of anesthesia and storage on posttranslational modifications of cardiac myofilament proteins. Issue 5 (7th May 2015) - Utter, Megan S.; Warren, Chad M.; Solaro, R. John
Abstract: Although high fidelity measurements of posttranslational modifications (PTMs) of cardiac myofilament proteins exist, important issues remain regarding basic techniques of sample acquisition and storage. We investigated the effects of anesthetic regimen and sample storage conditions on PTMs of major ventricular sarcomeric proteins. Mice were anesthetized with pentobarbital (Nembutal), ketamine/xylazine mixture (Ket/Xyl), or tribromoethanol (Avertin), and the ventricular tissue was prepared and stored for 1, 7, 30, 60, or 90 days at −80°C. Myofilament protein phosphorylation and glutathionylation were analyzed by Pro‐Q Diamond stain and Western blotting, respectively. With up to 7 days of storage, phosphorylation of troponin T was stable for samples from mice anesthetized with either Nembutal or Ket/Xyl but not Avertin; while myosin‐binding protein C (MyBP‐C) phosphorylation was reduced at 7 days with Nembutal and Ket/Xyl, though generally not significant until 90 days. Tropomyosin and regulatory myosin light chain phosphorylation were stable for up to 7 days regardless of the anesthetic regimen employed. In the case of Troponin I, by 7 days of storage there was a significant fall in phosphorylation across all anesthetics. Storage of samples from 30 to 90 days resulted in a general decrease in myofilament phosphorylation independent of the anesthetic. S‐glutathionylation of MyBP‐C presented a trend in reduced glutathionylation from days 30–90 in all anesthetics, with only day 90 being statistically significant. Our findings suggest that there are alterations in PTMs of major myofilament proteins from both storage and anesthetic selection, and that storage beyond 30 days will likely result in distortion of data. Abstract : Physiological control of the heart requires posttranslational modifications (PTMs) of major cardiac sarcomeric proteins. Studies of these modifications involve anesthetic regimens and sample storage, both of which have the potential to modify PTMs. Our findings demonstrate the relative advantage of a Ketamine/Xylazine mixture, versus Pentobarbital or Avertin. With regard to the stability of PTMs in myofibrils stored at −80°C, we found reduced phosphorylation and glutathionylation with extended storage of myofibrillar fractions beyond 30 days. In some cases, loss of phosphorylation occurred as early as 7 days in select proteins.